2017
DOI: 10.3906/sag-1705-8
|View full text |Cite
|
Sign up to set email alerts
|

Topographic methods to expose the exiting points of supratrochlear,supraorbital, and zygomaticotemporal nerves

Abstract: Background/aim: We evaluated the relations of the exiting points of supratrochlear (STN), supraorbital (SON), and zygomaticotemporal (ZTN) nerves with certain landmarks to provide improved anatomic knowledge. Materials and methods: The twenty-eight hemifaces of 5 fresh frozen and 11 embalmed heads (5 female and 11 male cadavers) were dissected. Distance and angular measurements were made between the exiting points of the nerves to the midline, lateral, and medial canthi. Comparisons of side, sex, and cadaver g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…However, they rendered the findings less reliable by making the measurements after dissection of the temporal region (Totonchi et al, 2005). A distance of 23.81 ± 4.8 mm between the exit point of the ZTN and the lateral canthus was found by Tezer et al during examination of 28 hemifaces of embalmed and fresh cadavers (Tezer et al, 2017). Last, based on our findings, we believe that some previous studies (Hauser & De Stefano, 1989) have misinterpreted a laterally exiting ZTF as a "high" zygomaticofacial foramen.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, they rendered the findings less reliable by making the measurements after dissection of the temporal region (Totonchi et al, 2005). A distance of 23.81 ± 4.8 mm between the exit point of the ZTN and the lateral canthus was found by Tezer et al during examination of 28 hemifaces of embalmed and fresh cadavers (Tezer et al, 2017). Last, based on our findings, we believe that some previous studies (Hauser & De Stefano, 1989) have misinterpreted a laterally exiting ZTF as a "high" zygomaticofacial foramen.…”
Section: Discussionmentioning
confidence: 98%
“…A thorough understanding of the pathway of the ZTN and its anatomical variations in terms of frequency and location of the ZTF is crucial for preventing iatrogenic injury during surgical manipulation in the region and for increasing the percentage of successful outcomes in neuro, plastic, and maxillofacial surgeries. However, there have been few studies of its anatomy, and reports in the literature rarely focus on the nerve and its topography (Tezer et al, 2017; Tubbs et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,[22][23][24] In contrast, it has been shown that there is no association between paranasal sinus volumes and headaches or facial pain. 25 In this regard, although the anatomic and morphometric features of the supraorbital region have been defined, 3,4,26,27 there is limited knowledge of FSV in migraine patients. Therefore, this study aimed to determine the FSV by 3D CT in patient groups with and without migraine and to identify their possible effects on migraine surgery.…”
mentioning
confidence: 99%
“…The needle embedding method is mainly characterized as detention to form later meridian inductive effects. The needles were placed in Baihui, Sishencong, Fengchi, Taichong, Yanglingquan, Sanyinjiao, Hegu, Ganshu, Shenshu and the chorea-trembling controlled area, which could nourish kidney and liver as well as stop endogenous wind [15,16] . By combining therapy of both methods, it is possible to nourish both kidney and liver, supplement body essence and marrow as well as stop endogenous wind and tremor.…”
mentioning
confidence: 99%